STRENGTHENING CONSUMER RIGHTS: CHALLENGES AND SOLUTIONS IN THE DIGITAL TRANSACTION ERA - Wina Paul; Dudi Badruzaman; Hasanudin; Anisa Mayasari (Gunung Djati Conference Series, 2024)
The growth of e-commerce and online transactions has changed the trade landscape, but has also raised a number of legal challenges regarding consumer rights. Through a juridical approach, this research explores various aspects of legal protection provided to consumers in online transactions, including applicable regulations, obligations of business actors, and dispute resolution mechanisms. The aim of this study is to analyze juridically the legal protection of consumers in online transactions and steps to prevent illegal practice procedures. Method The research was conducted qualitatively with normative juridical and utilized journals and relevant books. The study results show that Indonesia has several foundations laws that protect consumer rights in online transactions, namely legislation consumer protection, trade legislation, Ministerial Regulations Trade Number 53 of 2018 concerning Procedures for Resolving Consumer Disputes Electronically and Government Regulation Number 99 of 2018 concerning Protection Consumers Through Electronic Commerce. Consumers who feel disadvantaged online transactions can take legal steps to protect rights them, including reporting the case to the Consumer Dispute Resolution Agency (BPSK) or the online platform used. It is recommended for consumers to understand understand their rights when making online purchases and read the terms and conditionsonline transaction terms before making a purchase.